Experimenting with some variants of linear discriminant analysis - Khin Myo Myo Nyunt. (2008)
In this dissertation, we investigate the face recognition performance of Fisher's Linear Discriminant Analysis (LDA) and some weighted LDA extensions. Also, the effect of different LDA feature length on performance is also studied.